Platelet Rich Fibrin and Bone Graft in the Treatment of Intrabony Defect in Periodontitis Patients - Shrestha, Shilu; Shrestha, Surendra Man; Pradhan, Ameena; Aryal, Shreeya (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Background: Porous hydroxyapatite and β-tricalcium phosphate (β-TCP + HA) bone grafting material has resulted in clinically acceptable responses when used to fill the periodontal intrabony defects. PRF is an autologous leukocyte and platelet preparation that concentrates various polypeptide growth factors which therefore holds potential to be used as regenerative treatment for periodontal defects. Aim: The purpose of this study was to evaluate clinical and radiographic outcomes in periodontal intrabony defects treated with platelet rich fibrin compared to alloplastic bone graft material. Materials and Methods: Twenty subjects (10 subject per group, one site/subject) were treated either with platelet rich fibrin or alloplastic bone graft (30% β-TCP+ 70% HA). Primary clinical parameters: PD, CAL were taken at baseline, three months, six months and nine months post-operatively. Standardised radiographic data were collected at baseline, six months and nine months postoperatively. Results: Preoperative parameters were similar for both groups. Postsurgical measurements revealed a greater reduction in pocket depth in bone graft group (2.5 mm), greater CAL gain (2.2 mm) and greater defect fill (1.30 mm) as compared to platelet rich fibrin group (1.50 mm, 1.6 mm and 0.80 mm respectively ) at nine months. Conclusion: Treatment of intrabony defects with alloplast (30% β TCP+ 70% HA) or platelet rich fibrin both resulted in a significant probing depth reduction, CAL gain and bone depth reduction, with significantly better improvement in bone graft group.